TINGKAT KEPUASAN PENGGUNA LULUSAN PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN UNIVERSITAS NEGERI JAKARTA DI BIDANG NON KEPENDIDIKAN - R. Eka Murtinugraha; M. Agphin Ramadhan; Ulfatun Hasanah (LPPM Universitas Negeri Jakarta, 2020)
This research aims to determine the level of graduate user satisfaction with the performance graduates of the PTB FT UNJ Study Program in the non-educational field (construction services). This research was conducted in March to July 2019. This research was conducted to graduates of the PTB FT UNJ Study Program, the research method used was descriptive quantitative method, data collection techniques by distributing questionnaires / questionnaires to graduate users. The population in this research were 70 companies that became workplaces of 127 graduates working in the non-educational field. The sample in this research was 28 companies which were the workplaces of 37 graduates as engineers, estimators, and quantity surveyors assessed by 62 respondents both direct, indirect, and work partners of graduates. The results obtained from this research that the satisfaction of graduates in the ethical aspects of high, satisfaction in the aspect of expertise in the field of science is classified as moderate / sufficient, satisfaction in aspects of English proficiency is low / less, satisfaction of graduates in the aspects of technology & information is high, satisfaction in the aspect of communication ability classified as low / lacking, satisfaction in the aspect of teamwork is high and graduate user satisfaction in the aspect of self-development is classified as moderate / sufficient.